To Study the Pattern and Prevalence of Lipid Profile Abnormality in Newly Diagnosed Type 2 Diabetes Mellitus (Academia Journal of Medicine, 2019)
Background: Diabetes is one of the commonest chronic non communicable disease affecting the society at large both in developing and  developed countries. Present study aimed to study the Pattern and Prevalence of lipid profile abnormality in newly diagnosed type 2 diabetes  mellitus. Subjects and Methods: In this study, 100 newly diagnosed cases of type 2 diabetes mellitus patients were evaluated. A cross section  of both male and female diabetes patients diagnosed within the last 3 months (new onset) was taken into study. A detailed history, clinical  examination and relevant investigations were performed. Collected data were analysed by using appropriate software. Results: In our study  60% were male and 40% were female. Majority of cases were in the age group of 46-55 years, followed by in age group 56-65 years.  Dyslipidemia was present in 36.66% of male and 35 % of female. Highest prevalence of dyslipidemia was present in 56 -65 age group.  Hypertriglyceridemia was present in 33.33% of cases, Hypertriglyceridemia with low HDL-C was present in 33.33 % of cases,  Hypertriglyceridemia with low HDL-C and low LDL –C was present in 13.88% of cases while 19.44 % were having other mixed pattern of  dyslipidemia. Conclusion: Endeavour should be made to control hyperglycemia and hyperlipidia tightly by appropriate therapeutic measures  so that the occurrence and worsening of complications could be mitigated.
Keywords: Dyslipidemia; hyperglycemia; lipid profile